Large area, stretchable, wearable, screen-printed carbon heaters for use in elite sport - Andrew Claypole (Journal of Coatings Technology and Research, 2022)
Stretchable, nanocarbon heaters were screen-printed onto a stretchable film to create a passive heat maintenance device for elite sport. The heat uniformity and the temperature performance of these lightweight, large area electrothermal heaters were evaluated over a range of applied voltages using thermal imaging. The heaters provided a uniform heat over the 15 × 4 cm area with temperatures of 39°C, 54°C, and 72°C at 10, 15, and 20 V, respectively, within 150 s of being switched on. Tensile testing was used to examine the performance of the heaters under strain. At 20% nominal strain, the heaters gave a uniform heat output and a temperature of 44°C at 15 V, making it a promising candidate for wearable applications. The heaters were capable of maintaining temperatures of 40°C over 10 cyclic strains up to 10% nominal strain. The heaters were integrated into a proof-of-concept stretchable base-layer garment, with the effect of the heaters on skin temperature measured and thermal sensation evaluated during a simulated training session in an environmental chamber at an ambient temperature 0°C. The printed heaters maintained skin temperature and thermal sensation when compared with an unheated control.